Docetaxel and Lidocaine Co-Loaded (NLC-in-Hydrogel) Hybrid System Designed for the Treatment of Melanoma - Ludmilla David de Moura; Lígia N. M. Ribeiro; Fabíola V. de Carvalho; Gustavo H. Rodrigues da Silva; Priscila C. Lima Fernandes; Sérgio Q. Brunetto; Celso D. Ramos; Lício A. Velloso; Daniele R. de Araújo; Eneida de Paula (MDPI AG, 2021)
Melanoma is the most aggressive skin carcinoma and nanotechnology can bring new options for its pharmacological treatment. Nanostructured lipid carriers (NLC) are ideal drug-delivery carriers for hydrophobic drugs, such as the antineoplastic docetaxel (DTX), and hybrid (NLC-in-hydrogel) systems are suitable for topical application. This work describes a formulation of NLCDTX in xanthan-chitosan hydrogel containing lidocaine (LDC) with anticancer and analgesia effects. The optimized nanoparticles encapsulated 96% DTX and rheological analysis revealed inherent viscoelastic properties of the hydrogel. In vitro assays over murine fibroblasts (NIH/3T3) and melanoma cells (B16-F10), human keratinocytes (HaCaT) and melanoma cells (SK-MEL-103) showed reduction of docetaxel cytotoxicity after encapsulation in NLCDTX and HGel-NLCDTX. Addition of LDC to the hybrid system (HGel-NLCDTX-LDC) increased cell death in tumor and normal cells. In vivo tests on C57BL/6J mice with B16-F10-induced melanoma indicated that LDC, NLCDTX, HGel-NLCDTX-LDC and NLCDTX + HGel-LDC significantly inhibited tumor growth while microPET/SPECT/CT data suggest better prognosis with the hybrid treatment. No adverse effects were observed in cell survival, weight/feed-consumption or serum biochemical markers (ALT, AST, creatinine, urea) of animals treated with NLCDTX or the hybrid system. These results confirm the adjuvant antitumor effect of lidocaine and endorse HGel-NLCDTX-LDC as a promising formulation for the topical treatment of melanoma.